Efficacy of Forced-air Warming and Warmed Intravenous Fluid for Prevention of Hypothermia and Shivering During Caesarean Delivery Under Spinal Anaesthesia: A Randomized Controlled Trial. Issue 1 (March 2020) - Jun, J.; Chung, M.H.; Jun, I.; Kim, Y.; Kim, H.; Kim, J.H.; Choi, Y.R.; Choi, E.M.
Abstract : ( Eur J Anaesthesiol . 2019;36:442–448) Perioperative hypothermia and shivering are common in women undergoing cesarean delivery. Several complications have been associated with perioperative hypothermia, including surgical site infection and coagulopathy. During cesarean delivery maternal hypothermia may also lead to hypothermia in the newborn. The purpose of this prospective, randomized, controlled trial was to assess the effectiveness of preanesthetic forced-air warming combined with warmed intravenous (IV) fluid infusion to prevent maternal hypothermia and shivering in women receiving spinal anesthesia for undergoing cesarean delivery.